Fiber-reinforced geopolymer and drainage pipeline prepared from fiber-reinforced geopolymer
By using latex powder in EGC materials to form a cover layer, change the characteristics of the interface and improve the interface bonding, solve the problem of unstable performance of EGC materials, improve the mechanical performance and anti -penetration performance of small diameter drainage pipelines, realize environmental protection and environmental protection and Objective to cost benefits.
Patent Information
- Application Number
- CN202411423102.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The existing EGC materials are not very stable in performance due to the different activity of raw materials supplied, making it difficult to meet the high performance needs of small-diameter drainage pipes.
By forming a covering layer on the surface of the fiber or ground polymer raw material, the interface characteristics of the fiber and the ground polymer matrix are used using the latex powder to slow down the occurrence of polymerization reactions, improve the interface bonding between fiber and ground polymer matrix, and form a fiber - Latex powder -structure of the three of the ground polymer matrix.
It improves the fracture energy and bending toughness of fiber-reinforced geopolymers, enhances the impermeability and corrosion resistance of small-diameter drainage pipes, and reduces production costs and environmental pollution.
Smart Images

Figure CN119349933A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fiber-reinforced geopolymers, and in particular relates to a fiber-reinforced geopolymer and a drainage pipe prepared using the fiber-reinforced geopolymer. Background Art
[0002] Nowadays, the demand for cement is increasing in various sectors such as residential, commercial and industrial buildings. 50% of the CO2 emitted by the cement industry comes from the calcination process of limestone, and the remaining 50% comes from the combustion of fuel in the kiln, transportation and electricity used in manufacturing operations. The type of fuel used in cement production affects the CO2 emissions. Measures should be taken to reduce air pollution and global warming. Using cement substitutes to make concrete is a fair starting point for reducing concrete CO2 emissions. Cement substitutes can be varied such as fly ash, ground blast furnace slag (GGBS), rice husk ash, metakaolin, etc. Alternatives to industrial waste should be considered.
[0003] Replacing 100% of cement with these industrial byproducts will help utilize the growing waste streams and achieve carbon reduction targets faster. Fiber-reinforced geopolymers (EGC) are produced from industrial waste / byproducts (fly ash, mineral powder). Materials with high silicon and aluminum content are selected to produce EGC. Single or combination of two or more materials are used. Fine and coarse aggregates are selected as required. Geopolymer concrete is mixed with alkaline solution. Alkaline solution is prepared by adding sodium silicate or potassium silicate and sodium hydroxide or potassium hydroxide. Suitable organic fibers are then added. At this stage, for problems such as shrinkage cracking of EGC, glue powder can be added to alleviate them. Finally, according to the mix design, all the ingredients are mixed. Then the geopolymer concrete is cured by thermal curing or ambient curing methods. The hardening reaction mechanism of geopolymer is the condensation of oligomeric potassium (silicate-siloxane) into a polymeric potassium (silicate-siloxane) cross-linked network.
[0004] The carbon emission during the preparation of 1kg of geopolymer cement is 0.18kg, which is only 24% of ordinary Portland cement; at the same time, the energy consumption during the production process is lower, accounting for only 30% of the energy consumption of cement production year-on-year. If the activity of solid waste is improved, its energy consumption can be reduced to 10% of cement production. Studies have shown that EGC has excellent mechanical properties, fire resistance, high temperature resistance, corrosion resistance and good impermeability, and is favored by scientific researchers. It is believed that it can replace cement or serve as a supplement to cement materials in some fields.
[0005] With the continuous advancement of the urban underground integrated pipe gallery system, the construction of underground pipelines has higher standards, and the selection of suitable pipe gallery materials is of utmost importance. In particular, many northern cities in my country are seriously short of water. At present, the main types of underground pipelines in my country are concrete pipes and plastic pipes. Concrete pipes are easily corroded by sewage during use as drainage pipes, causing pipe leakage and water seepage, so their service life is often insufficient; and concrete pipes have a large deadweight, poor wear resistance, high roughness, high breakage rate, and weak water-passing capacity. The manufacturing cost of plastic pipes is high, and the quality is prone to unevenness during the manufacturing process; and the plastic pipes themselves are light in weight and have insufficient ring stiffness. They are prone to breakage or even collapse when the external pressure is too high; during the use of plastic drainage pipes, the pipes may be affected by chemicals in sewage and age, causing the pipes to harden, become brittle, or even crack. Therefore, plastic pipes need to be inspected and repaired regularly during use, resulting in increased costs for manual maintenance.
[0006] How to use EGC to make small-diameter drainage pipes is a technical problem that researchers need to solve urgently. Compared with ordinary cement, using EGC to make small-diameter drainage pipes is not only cheaper, but also less polluting to the environment, solid waste utilization, green production, and in line with the country's carbon peak and carbon neutrality strategies. However, the performance of existing EGC materials is not very stable due to the different activities of the raw materials supplied. Summary of the invention
[0007] The purpose of the present invention is to provide a fiber reinforced geopolymer and a drainage pipe prepared therefrom in view of the above-mentioned deficiencies in the prior art, wherein latex powder is dissolved in water after being added to form a coating layer wrapped around the surface of the fiber or geopolymer raw material, thereby changing the interface characteristics of the fiber and the geopolymer matrix, slowing down the occurrence of the polymerization reaction, causing the mechanical properties of the EGC material to decrease, and at the same time improving the interface bonding between the fiber and the geopolymer matrix, forming a synergistic structure of the fiber-latex powder-geopolymer matrix, increasing the fracture energy of the fiber reinforced geopolymer, and improving the bending toughness of the fiber reinforced geopolymer.
[0008] To achieve the above object, the present invention adopts the following technical solution:
[0009] The first object of the present invention is to provide a fiber-reinforced geopolymer, comprising the following components by mass: 250-300 parts of mineral powder, 200-220 parts of fly ash, 670-730 parts of quartz sand, 120-150 parts of alkali activator, 7.6-24 parts of fiber, 3.5-34.9 parts of latex powder and 20.9-41.9 parts of rubber powder, and also comprising the following preparation steps: adding mineral powder and fly ash in a cement mortar mixer in sequence, stirring at a low speed, and mixing evenly; slowly adding fiber while stirring and dry mixing for a first preset time, then adding quartz sand, latex powder and rubber powder, and adding water and stirring evenly, so as to obtain the fiber-reinforced geopolymer.
[0010] Furthermore, the fiber is at least one of polyvinyl alcohol fiber, polypropylene fiber and polyoxymethylene fiber.
[0011] Furthermore, the latex powder is PVA latex powder or VAE latex powder.
[0012] Furthermore, the mineral powder is selected from S95 grade ground slag powder with a density of 2.88g / cm 3 , with a specific surface area of 440m 2 / kg.
[0013] Furthermore, the fly ash is selected from Grade II fly ash with a density of 2.24 g / cm 3 , with a specific surface area of 400m 2 / kg.
[0014] Furthermore, the fiber content is a wet bulk volume content, and the fiber is a polyvinyl alcohol fiber.
[0015] Furthermore, the mass concentration ratio of the VAE latex powder and the rubber powder is (3-5):3, wherein the VAE latex powder is added in proportion based on the total mass of the mineral powder and the fly ash, and the rubber powder is added in proportion based on the mass of the quartz sand.
[0016] Furthermore, the particle size of the quartz sand is 20 to 40 meshes.
[0017] The second object of the present invention is to provide the use of the fiber-reinforced geopolymer in the preparation of building materials.
[0018] The third object of the present invention is to provide a drainage pipe. The fiber-reinforced geopolymer is poured into a prefabricated pipe mold, bubbles are removed, and the mold is demoulded and cured for 7 to 28 days to obtain the drainage pipe.
[0019] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0020] (1) Compared with other fiber-reinforced geopolymers, the present invention adds latex powder and rubber powder to modify the engineering geopolymer composite material, which effectively improves the poor dispersion of fiber in geopolymer when the fiber content is large, improves the toughness and deformation capacity of fiber-reinforced geopolymer, and the fracture energy increase of the group with rubber powder is more than 50% compared with that without rubber powder. After being added, the latex powder dissolves in water to form a coating layer wrapped around the surface of the fiber or geopolymer raw material, which changes the interface characteristics of the fiber and the geopolymer matrix, slows down the occurrence of the geopolymerization reaction, and reduces the mechanical properties of the EGC material. At the same time, it improves the interface bonding between the fiber and the geopolymer matrix, forming a synergistic structure of fiber-latex powder-geopolymer matrix, increasing the fracture energy of the fiber-reinforced geopolymer, and improving the bending toughness of the fiber-reinforced geopolymer.
[0021] (2) The fiber-reinforced geopolymer provided by the present invention uses industrial waste / by-products such as fly ash and mineral powder, providing a new path to solve the accumulation of solid waste. The carbon emission during the production of 1kg of geopolymer cement is 0.18kg, which is only 24% of ordinary Portland cement; at the same time, the energy consumption in the production process is lower, accounting for only 30% of the energy consumption of cement production year-on-year, responding to the national energy conservation and emission reduction, carbon peak and carbon neutrality strategy.
[0022] (3) Compared with other small-diameter drainage pipe materials, fiber-reinforced geopolymers have lower costs, higher density, doubled impermeability, and improved long-term corrosion resistance inside and outside the pipe. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1a A comparison chart of the coagulation time of the single-mixed rubber powder provided by the present invention;
[0024] Figure 1b A comparison chart of the setting time of the single VAE latex powder mortar provided by the present invention;
[0025] Figure 1c A comparison chart of the setting time of the single-doped PVA latex powder mortar provided by the present invention;
[0026] Figure 2 A comparison chart of the coagulation time of the mixed VAE latex powder and rubber powder provided by the present invention;
[0027] Figure 3 A comparison chart of the coagulation time of the mixed PVA latex powder and rubber powder provided by the present invention;
[0028] Figure 4 A comparison chart of the fluidity of the mixed VAE latex powder and rubber powder mortar provided by the present invention;
[0029] Figure 5A comparison chart of the fluidity of mixed PVA latex powder and rubber powder provided by the present invention;
[0030] Figure 6 A comparison chart of the 28-day compressive strength of the mixed VAE latex powder and rubber powder mortar provided by the present invention;
[0031] Figure 7 A comparison chart of the 28-day flexural strength of the mixed VAE latex powder and rubber powder mortar provided by the present invention;
[0032] Figure 8 A comparison chart of the compression ratios of the mixed VAE latex powder and rubber powder mortar provided by the present invention after 28 days;
[0033] Fig. 9 A comparison chart of the 28-day compressive strength of the mixed PVA latex powder and rubber powder mortar provided by the present invention;
[0034] Fig.10 A comparison chart of the 28-day flexural strength of the mixed PVA latex powder and rubber powder mortar provided by the present invention;
[0035] Fig.11 A comparison chart of the compression ratios of the mixed PVA latex powder and rubber powder mortar provided by the present invention after 28 days;
[0036] Fig.12a The load-deflection curves of the mortar mixed with 3% VAE latex powder and 3% rubber powder provided by the present invention after 28 days of mixing;
[0037] Figure 12b The load-deflection curves of the mortar mixed with 5% VAE latex powder and 3% rubber powder provided by the present invention after 28 days of mixing;
[0038] Fig.13a The load-deflection curves of the mortar mixed with 1% PVA latex powder and 3% rubber powder provided by the present invention after 28 days of mixing;
[0039] Fig.13b The load-deflection curve of the mortar mixed with 2% PVA latex powder and 3% rubber powder for 28 days
[0040] Fig.14a This is a SEM image of the PVA1 group without glue powder provided by the present invention;
[0041] Fig.14b This is a SEM image of a 7-day PVA1 group when 3% VAE latex powder is added provided by the present invention;
[0042] Fig.14c The SEM image of the 7-day PVA1 group when 1% PVA latex powder is added provided by the present invention;
[0043] Fig.15 A pipe cross-sectional view of a small diameter drainage pipe provided by the present invention;
[0044] Fig.16 A longitudinal cross-sectional view of a small-diameter drainage pipe provided by the present invention;
[0045] Fig.17 This is a diagram of the overall structure of the small-diameter drainage pipe provided by the present invention. DETAILED DESCRIPTION
[0046] To make the present invention easier to understand, the present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. Unless otherwise defined, the professional terms used below are consistent with the meanings understood by professional and technical personnel in the field; unless otherwise specified, the raw materials and reagents involved in this article can be purchased from the market or prepared by known methods.
[0047] In order to solve the performance defects of existing small-diameter drainage pipes, the concrete pipes have a large dead weight, poor wear resistance, high roughness, high breakage rate, and weak water flow capacity. The present invention provides a stable EGC material specially for small-diameter drainage pipes.
[0048] The invention adopts geopolymer raw materials, quartz sand, fiber, latex powder, rubber powder, alkali activator and water to prepare latex powder / rubber powder modified engineering geopolymer composite materials, and at the same time studies the working performance of VAE latex powder, PVA latex powder and rubber powder in the engineering geopolymer composite materials in the state of single mixing or mixing, and develops EGC materials suitable for small diameter drainage pipes.
[0049] EGC powder materials are selected from mineral powder and fly ash. The mineral powder is selected from S95 grade ground slag powder with a density of 2.88g / cm 3 , with a specific surface area of 440m 2 / kg. Fly ash is selected from Grade II fly ash, with a density of 2.24g / cm 3 , with a specific surface area of 400m 2 / kg, and their chemical compositions are shown in Table 1.
[0050] Table 1. Composition of mineral powder and fly ash.
[0051]
[0052] Water glass (sodium silicate solution) and industrial grade NaOH particles are used to prepare the alkali activator. The modulus of water glass is 3.23, and its main parameters are shown in Table 2. The purity of industrial grade NaOH is 99%. The preparation method of the composite alkali activator is as follows: NaOH particles are added to water glass, and the water glass is prepared into a 1.5 modulus alkali activator by adding NaOH content. The 1.5 modulus composite alkali activator requires adding 10.58g of NaOH particles to 100g of original sodium water glass solution.
[0053] Table 2. Sodium water glass parameters (wt.%)
[0054]
[0055] EGC uses polyvinyl alcohol fiber (PVA fiber), and the basic properties of the fiber are shown in Table 3. The fiber length is 12mm.
[0056] Table 3. Basic properties of PVA fibers
[0057]
[0058] EGC sand is made of quartz sand, which is a silicate mineral. Its main mineral component is SiO2. The color of quartz sand is milky white, colorless and translucent, with a hardness of 7 and a density of 2.65. The particle size of quartz sand is 20-40 mesh.
[0059] The water used for the material is tap water.
[0060] The following is a detailed description of a method for preparing a fiber-reinforced geopolymer provided by the present application in conjunction with specific embodiments and comparative examples.
[0061] Example 1
[0062] This embodiment provides a fiber-reinforced geopolymer, which is prepared by using the above method using only rubber powder.
[0063] Rubber powder is used as sand in engineering geopolymer composite materials, so the amount of rubber powder is added according to the mass ratio of quartz sand. The designed rubber powder addition amount is divided into two levels of 3% and 6%. The mortar mix ratio of rubber powder alone is shown in Table 4.
[0064] Table 4. Rubber powder single-mixed mortar mix ratio (unit: g)
[0065]
[0066] It should be noted that the fiber content is added by volume, and the rubber powder is added in the mass proportion of quartz sand.
[0067] Test 1-1: The rubber powder added was 3% rubber powder; the fiber added was 1% PVA fiber.
[0068] Test 1-2: The rubber powder added was 3% rubber powder; the fiber added was 2% PVA fiber.
[0069] Test 1-3: The rubber powder added was 3% rubber powder; the fibers added were 1% PP fiber and 1% PVA fiber.
[0070] Test 1-4: The rubber powder added was 3% rubber powder; the fibers added were 1% POM fiber and 1% PVA fiber.
[0071] Test 1-5: The rubber powder added was 6% rubber powder; the fiber added was 1% PVA fiber.
[0072] Test 1-6: The rubber powder blended was 6% rubber powder; the fiber blended was 2% PVA fiber.
[0073] Test 1-7: The rubber powder blended was 6% rubber powder; the fibers blended were 1% PP fiber and 1% PVA fiber.
[0074] Test 1-8: The rubber powder blended was 6% rubber powder; the fibers blended were 1% POM fiber and 1% PVA fiber.
[0075] Example 2
[0076] This embodiment provides a fiber-reinforced geopolymer, which is prepared by using the above method using single-doped VAE latex powder.
[0077] Based on the previous design of the composition of the engineering geopolymer composite material by the inventor, two levels of 3% and 5% VAE latex powder were designed to analyze and determine the effect of VAE latex powder on the engineering geopolymer composite material. The mortar mix ratios with different VAE latex powder dosages are shown in Table 5.
[0078] Table 5. VAE latex powder single mortar mix ratio (unit: g)
[0079]
[0080] It should be noted that the fiber content is added by volume, and the VAE latex powder is added by the mass ratio of mineral powder and fly ash.
[0081] Test 2-1: No VAE latex powder was added, and the fiber added was 1% PVA fiber.
[0082] Test 2-2: No VAE latex powder was added; the fiber added was 2% PVA fiber.
[0083] Test 2-3: No VAE latex powder was added; the fibers added were 1% PP fiber and 1% PVA fiber.
[0084] Test 2-4: No VAE latex powder was added; the fibers added were 1% POM fiber and 1% PVA fiber.
[0085] Test 2-5: The blended rubber powder is 3% VAE latex powder; the blended fiber is 1% PVA fiber.
[0086] Test 2-6: The blended rubber powder is 3% VAE latex powder; the blended fiber is 2% PVA fiber.
[0087] Test 2-7: The blended rubber powder is 3% VAE latex powder; the blended fibers are 1% PP fiber and 1% PVA fiber.
[0088] Test 2-8: The blended rubber powder is 3% VAE latex powder; the blended fibers are 1% POM fiber and 1% PVA fiber.
[0089] Test 2-9: The rubber powder added was 5% VAE latex powder; the fiber added was 1% PVA fiber.
[0090] Test 2-10: The blended rubber powder is 5% VAE latex powder; the blended fiber is 2% PVA fiber.
[0091] Test 2-11: The blended rubber powder is 5% VAE latex powder; the blended fibers are 1% PP fiber and 1% PVA fiber.
[0092] Test 2-12: The blended rubber powder is 5% VAE latex powder; the blended fibers are 1% POM fiber and 1% PVA fiber.
[0093] Example 3
[0094] This embodiment provides a fiber-reinforced geopolymer, which is prepared by using the above method using a single-doped PAE latex powder.
[0095] Four levels of PVA latex powder were selected, namely 0.5%, 1%, 1.5% and 2%, to analyze and determine the effect of PVA latex powder on engineering geopolymer composites. The mortar mix ratios with different VAE latex powder dosages are shown in Table 6.
[0096] Table 6. PVA latex powder single mortar mix ratio (unit: g)
[0097]
[0098] It should be noted that the fiber content is added by volume, and the PVA latex powder is added by the mass ratio of mineral powder and fly ash.
[0099] Test 3-1: The rubber powder added was 0.5% PVA latex powder; the fiber added was 1% PVA fiber.
[0100] Test 3-2: The rubber powder added was 0.5% PVA latex powder; the fiber added was 2% PVA fiber.
[0101] Test 3-3: The rubber powder added was 0.5% PVA latex powder; the fibers added were 1% PP fiber and 1% PVA fiber.
[0102] Test 3-4: The rubber powder added was 0.5% PVA latex powder; the fibers added were 1% POM fiber and 1% PVA fiber.
[0103] Test 3-5: The rubber powder added was 1% PVA latex powder; the fiber added was 1% PVA fiber.
[0104] Test 3-6: The rubber powder added was 1% PVA latex powder; the fiber added was 2% PVA fiber.
[0105] Test 3-7: The rubber powder added was 1% PVA latex powder; the fibers added were 1% PP fiber and 1% PVA fiber.
[0106] Test 3-8: The rubber powder added was 1% PVA latex powder; the fibers added were 1% POM fiber and 1% PVA fiber.
[0107] Test 3-9: The rubber powder added was 1.5% PVA latex powder; the fiber added was 1% PVA fiber.
[0108] Test 3-10: The rubber powder added was 1.5% PVA latex powder; the fiber added was 2% PVA fiber.
[0109] Test 3-11: The blended rubber powder is 1.5% PVA latex powder; the blended fibers are 1% PP fiber and 1% PVA fiber.
[0110] Test 3-12: The rubber powder added was 1.5% PVA latex powder; the fibers added were 1% POM fiber and 1% PVA fiber.
[0111] Test 3-13: The rubber powder added was 2% PVA latex powder; the fiber added was 1% PVA fiber.
[0112] Test 3-14: The rubber powder added was 2% PVA latex powder; the fiber added was 2% PVA fiber.
[0113] Test 3-15: The rubber powder added was 2% PVA latex powder; the fibers added were 1% PP fiber and 1% PVA fiber.
[0114] Test 3-16: The rubber powder added was 2% PVA latex powder; the fibers added were 1% POM fiber and 1% PVA fiber
[0115] Example 4
[0116] This embodiment provides a fiber-reinforced geopolymer, which is prepared by mixing VAE latex powder and rubber powder and adopting the above method.
[0117] According to relevant literature and previous experimental results, the inventor selected two dosages of VAE latex powder of 3% and 5%, and the dosage of rubber powder was selected as 3%; at the same time, the selected fiber ratios were the four optimized ratios of PVA 1vol%, PVA 2vol%, PP 1vol% plus PVA 1vol%, and POM 1vol% plus PVA 1vol%, so the mortar ratio of VAE latex powder and rubber powder is shown in Table 7.
[0118] Table 7.
[0119]
[0120] It should be noted that the fiber content is added by volume, and the rubber powder is added by the mass ratio of mineral powder and fly ash.
[0121] Test 4-1: The mixed rubber powder added was 3% VAE latex powder and 3% rubber powder; the fiber added was 1% PVA fiber.
[0122] Test 4-2: The mixed rubber powder added was 3% VAE latex powder and 3% rubber powder; the fiber added was 2% PVA fiber.
[0123] Test 4-3: The mixed rubber powder added was 3% VAE latex powder and 3% rubber powder; the fibers added were 1% PP fiber and 1% PVA fiber.
[0124] Test 4-4: The mixed rubber powder added was 3% VAE latex powder and 3% rubber powder; the fibers added were 1% POM fiber and 1% PVA fiber.
[0125] Test 4-5: The mixed rubber powder added was 5% VAE latex powder and 3% rubber powder; the fiber added was 1% PVA fiber.
[0126] Test 4-6: The mixed rubber powder added was 5% VAE latex powder and 3% rubber powder; the fiber added was 2% PVA fiber.
[0127] Test 4-7: The mixed rubber powder added was 5% VAE latex powder and 3% rubber powder; the fibers added were 1% PP fiber and 1% PVA fiber.
[0128] Test 4-8: The mixed rubber powder added was 5% VAE latex powder and 3% rubber powder; the fibers added were 1% POM fiber and 1% PVA fiber.
[0129] Example 5
[0130] This embodiment provides a fiber-reinforced geopolymer, which is prepared by mixing PAE latex powder and rubber powder and adopting the above method. The mortar formula of the PAE latex powder and rubber powder is shown in Table 8.
[0131] Table 8.
[0132]
[0133] It should be noted that the fiber dosage is an external dosage by volume, the dosage of PVA latex powder is calculated based on the total mass of mineral powder and fly ash, and the dosage of rubber powder is calculated based on the mass of quartz sand.
[0134] Test 5-1: The mixed rubber powder added was 1% PAE latex powder and 3% rubber powder; the fiber added was 1% PVA fiber.
[0135] Test 5-2: The mixed rubber powder added was 1% PAE latex powder and 3% rubber powder; the fiber added was 2% PVA fiber.
[0136] Test 5-3: The mixed rubber powder added was 1% PAE latex powder and 3% rubber powder; the fibers added were 1% PP fiber and 1% PVA fiber.
[0137] Test 5-4: The mixed rubber powder added was 1% PAE latex powder and 3% rubber powder; the fibers added were 1% POM fiber and 1% PVA fiber.
[0138] Test 5-5: The mixed rubber powder added was 2% PAE latex powder and 3% rubber powder; the fiber added was 1% PVA fiber.
[0139] Test 5-6: The mixed rubber powder added was 2% PAE latex powder and 3% rubber powder; the fiber added was 2% PVA fiber.
[0140] Test 5-7: The mixed rubber powder added was 2% PAE latex powder and 3% rubber powder; the fibers added were 1% PP fiber and 1% PVA fiber.
[0141] Test 5-8: The mixed rubber powder added was 2% PAE latex powder and 3% rubber powder; the fibers added were 1% POM fiber and 1% PVA fiber.
[0142] Comparative Example 1
[0143] This comparative example provides a fiber-reinforced geopolymer without rubber powder.
[0144] It is basically the same as Experiment 1 in Example 1, except that no rubber powder is added.
[0145] In order to better illustrate the performance of the fiber-reinforced geopolymer provided by the present invention, the applicant conducted the following studies on Examples 1-4 and Comparative Examples:
[0146] (1) Study on coagulation time
[0147] The setting time of the composite material is tested using a Vicat apparatus. The timing starts from the addition of water. After the composite material is stirred, it is poured into the test mold. When the test needle sinks to 4±1mm from the bottom plate, the specimen is at this time of initial setting time. The mold is turned over, and after the test needle is replaced, the time when the test needle cannot leave any mark on the composite material is the final setting time.
[0148] refer to Figure 1a , is the setting time of fiber reinforced geopolymer with rubber powder alone. It can be found from the figure that compared with the case without rubber powder, the effect of different amounts of rubber powder alone on the setting time of fiber reinforced geopolymer mortar is not significant. When 3% rubber powder is added, under the four fiber dosage ratios, the setting time of fiber reinforced geopolymer mortar is only slightly extended, and the extension range is about 3%. When 6% rubber powder is added, the setting time of fiber reinforced geopolymer mortar has no significant change compared with the case without rubber powder. The PVA1 group and PP1+1 group have an extension of about 8%, and the PVA2 group and POM1+1 group have no significant change.
[0149] refer to Figure 1b , is the setting time of fiber reinforced geopolymer with single VAE latex powder. Compared with the three ratios of no glue powder group, 3% VAE latex powder and 5% VAE latex powder, the shortest setting time is PVA2 group, while the setting time of the other three groups such as PVA1, PP1+1 and POM1+1 is not much different. With the increase of VAE latex powder content, the setting time gradually increases, and the largest change is in PVA1 group, which extends from 38min without glue powder to 48min with 5% VAE latex powder.
[0150] refer to Figure 1c, is the setting time of fiber reinforced geopolymer mortar with single PVA latex powder. It can be seen from the figure that with the increase of PVA latex powder content, the setting time of fiber reinforced geopolymer mortars of various proportions is extended to varying degrees. The setting time of the mortar of the PVA1 group was extended from 38 min without glue powder to 46 min when the PVA latex powder content was 2%, the setting time of the PVA2 group was extended from 33 min without glue powder to 41 min when the PVA latex powder content was 2%, the setting time of the PP1+1 group was extended from 37 min to 48 min with the addition of 2% PVA latex powder, and the setting time of the POM1+1 group was extended from 39 min without the addition of glue powder to 48 min with the addition of 2% PVA latex powder. This indicates that the addition of PVA latex powder will delay the setting time of the engineering geopolymer composite material to a certain extent. This may be because the addition of PVA latex powder causes the rheological properties of the engineering geopolymer composite material mortar to change, thereby delaying the setting time of the engineering geopolymer composite material mortar.
[0151] Will Figure 1a , 1b Compared with 1c, it can be found that the effect of single rubber powder on the setting time of fiber reinforced geopolymer is much smaller than that of single VAE latex powder and single PVA latex powder.
[0152] refer to Figure 2 , is the setting time of fiber reinforced geopolymer when VAE latex powder and rubber powder are mixed. It can be seen from the figure that when the rubber powder content is kept at 3%, the setting time of fiber reinforced geopolymer is significantly extended with the increase of VAE latex powder content. The coagulation time of the PVA1 group was extended from 38 min without added rubber powder to 46 min with 3% VAE latex powder and 3% rubber powder, and then to 48 min with 5% VAE latex powder and 3% rubber powder, with an increase of 26%; the coagulation time of the PP1+1 group was extended from 37 min without rubber powder to 47 min with 5% VAE latex powder and 3% rubber powder, with an increase of 27%; the POM group had the smallest increase, from 39 min to 45 min with 5% VAE latex powder and 3% rubber powder, with an increase of only 15%, which is much smaller than that of the PVA1 group, PVA2 group and PP1+1 group. This may be because the interaction between VAE latex powder and POM fiber is different from that between PVA fiber and PP fiber.
[0153] from Figure 2It can also be found that compared with the fiber-reinforced geopolymer mixed with VAE latex powder alone, the effect of mixed VAE latex powder and rubber powder on the setting time of fiber-reinforced geopolymer mortar is almost the same, with no obvious difference, and the growth range of setting time in each group has no large fluctuation, which shows that the effect of rubber powder on setting time is small. This may be because rubber powder mainly acts as fine aggregate and fills in fiber-reinforced geopolymer mortar; while VAE latex powder changes the surface properties of various components in the composite material in fiber-reinforced geopolymer mortar, delaying the setting time of fiber-reinforced geopolymer.
[0154] refer to Figure 3 , is the setting time of fiber reinforced geopolymer mortar when mixed with PVA latex powder and rubber powder. The setting time of each group varies greatly. The setting time of PVA1 group is extended from 38min without glue powder to 44min with 1% PVA latex powder and 3% rubber powder, and then to 48min with 2% PVA latex powder and 3% rubber powder; the setting time of PVA2 group is delayed from 33min without glue powder to 42min with 2% PVA latex powder and 3% rubber powder; the setting time of PP1+1 group is extended from 37min at the beginning to 44min with 1% PVA latex powder and 3% rubber powder, and then to 51min with 2% PVA latex powder and 3% rubber powder; the setting time of POM1+1 group is extended from 39min to 45min, and finally to 49min with 2% PVA latex powder and 3% rubber powder. By comparing the setting time of fiber reinforced geopolymer mortar mixed with PVA latex powder and rubber powder with the setting time of single PVA latex powder and single rubber powder, it can be found that the rubber powder has little effect on the setting time, and more importantly, the effect of PVA latex powder on the setting time of fiber reinforced geopolymer mortar.
[0155] (2) Fluidity research
[0156] The fluidity of the engineering geopolymer composite material slurry and mortar was tested by truncated cone round mold. For the slurry, a truncated cone round mold with an upper diameter of 36mm, a lower diameter of 60mm, and a height of 60mm was used; for the mortar, a truncated cone round mold with an upper diameter of 60mm, a lower diameter of 100mm, and a height of 60mm was used. Pour the mixed composite material into the truncated cone round mold, scrape the upper surface flat, lift the truncated cone round mold vertically, and use a steel ruler to measure the diameters in two perpendicular directions, and take the average value as the fluidity of the composite material.
[0157] refer to Figure 4, is the fluidity of fiber reinforced geopolymer mortar mixed with VAE latex powder and rubber powder. As can be seen from the figure, with the addition of rubber powder, the fluidity of the composite material shows a significant decrease. Among them, the fluidity of the PVA1 group dropped from 194mm to 180mm and then to 173mm, and the fluidity decreased by 10.84%. The fluidity of the PVA2 group dropped directly from 127mm to loss of fluidity. The fluidity of the PP1+1 group dropped from 231mm without rubber powder to 215mm mixed with 5% VAE latex powder and 3% rubber powder, with a decrease of 6.93%. The decrease in the fluidity of the POM1+1 group of 220m was only higher than that of the PP1+1 group, with a decrease of 9.87%. From the fluidity data analysis of each fiber ratio, it can be seen that the mixed VAE latex powder and rubber powder will have a greater impact on the fluidity. By comparing the fluidity results of the mixed VAE latex powder and rubber powder with the fluidity results of single VAE latex powder and single rubber powder, it can be found that for the fluidity of fiber reinforced geopolymer mortar, VAE latex powder plays a major role in the decrease of fluidity. This may be because compared with rubber powder, VAE latex powder will dissolve in water and then bond with the mortar material, thereby increasing the overall viscosity of the composite mortar, while rubber powder only slightly increases the water demand of the composite material and does not change the rheological properties of the mortar.
[0158] refer to Figure 5 , is the fluidity of fiber reinforced geopolymer mortar mixed with PVA latex powder and rubber powder. As can be seen from the figure, with the addition of PVA latex powder and rubber powder, the fluidity of the composite mortar gradually decreases. Among the four fiber ratios, the largest decrease is in the PVA2 group, which is 17.32%, while the smallest decrease is in the PP1+1 group, which is only 6.06%. The decrease in fluidity of the PVA1 group and the POM1+1 group is between 9% and 10%. Compared with the fluidity of the composite mortar mixed with VAE latex powder and rubber powder, it can be found that, except for the POM1+1 group, the decrease in fluidity of the other three fiber ratios is less than that of the groups mixed with VAE latex powder and rubber powder. This shows that when 2% PVA latex powder and 3% rubber powder are mixed, the decrease in fluidity is less than when 5% VAE latex powder and 3% rubber powder are mixed. The effect of mixing PVA latex powder and rubber powder on fluidity shows that PVA latex powder has a greater influence on the fluidity of composite mortar. This may be because PVA latex powder will dissolve in water and adsorb on the surface of mineral powder, fly ash or fiber, thereby hindering the sliding between the components in the slurry, thereby affecting the fluidity of the composite mortar.
[0159] (3) Compressive strength research
[0160] Six test blocks after the flexural strength test were taken for compressive strength test. The compressive strength test was also carried out by a flexural and compression integrated testing machine, with a load pressure speed of 1000N / s±100N / s, and the average of a group of six compressive strength measurement values was taken as the experimental result.
[0161] refer to Figure 6 , is the compressive strength of each fiber ratio at 28 days when VAE latex powder and rubber powder are mixed. As can be seen from the figure, in the case of mixing different rubber powders, the PP1+1 group has the highest strength among the four fiber ratios, which are 66.2MPa and 61.7MPa respectively. When 3% VAE latex powder and 3% rubber powder are mixed, the PP1+1 group has the largest decrease in compressive strength at 28 days, which is 11.26%, and the PVA1 group has the smallest decrease, which is 9.45%. When 5% VAE latex powder and 3% rubber powder are mixed, the POM1+1 group has the largest decrease in compressive strength at 28 days.
[0162] refer to Fig. 9 , is the 28-day compressive strength of four fiber ratios when mixed with PVA latex powder and rubber powder. As can be seen from the figure, when different amounts of PVA latex powder and rubber powder are mixed, the PP1+1 group has the largest compressive strength, which are 66.3MPa and 62.1MPa respectively. When 1% of PVA latex powder and 3% of rubber powder are added, the PP1+1 group has the largest decrease in 28-day compressive strength, with a decrease of 11.13%, and the decreases of the other three fibers are between 9% and 10%. When 2% of PVA latex powder and 3% of rubber powder are added, the POM1+1 group has the largest decrease in compressive strength.
[0163] (4) Study on flexural strength
[0164] The 40mm×40mm×160mm prism specimens cured to the corresponding age were taken out from the constant temperature and humidity curing box, and the flexural strength test was carried out using a flexural and compression integrated testing machine. The flexural test loading speed was 50N / s±5N / s, and the average flexural strength of a group of three prism specimens was taken as the experimental result. When the strength of one of the three prism specimens is outside the range of ±15% of the mean, this data was removed and the mean was recalculated; when the strength of two of the three prism specimens is outside the range of ±15% of the mean, this group of data is invalid, and the specimens of this ratio should be taken again for testing.
[0165] refer to Figure 7, is the 28-day flexural strength when mixed with VAE latex powder and rubber powder. It can be found from the figure that the degree of decrease in flexural strength of composite materials with different fiber ratios is inconsistent when mixed with different amounts of rubber powder. When 3% VAE latex powder and 3% rubber powder are added, the flexural strength of PVA1 group and PVA2 group decreases slightly, between 3% and 3.2%, while the decrease in POM1+1 group reaches 7.61%; when 5% VAE latex powder and 3% rubber powder are added, the largest decrease is in PVA2 group, which is 13.40%.
[0166] refer to Fig.10 The figure shows the 28-day flexural strength of the composite mortar when mixed with PVA latex powder and rubber powder. It can be seen from the figure that when 1% PVA latex powder and 3% rubber powder are added, the PVA2 group has the highest flexural strength, which is 9.3MPa. At this time, the PVA1 group has the largest decrease in flexural strength among the four fiber ratios, which is 6.38%; when 2% PVA latex powder and 3% rubber powder are added, the PP1+1 group has the highest flexural strength, the PVA2 group has the largest decrease in flexural strength, and the PP1+1 group has the smallest decrease.
[0167] (5) Study on compressive strength ratio
[0168] The 40mm×40mm×160mm prism specimens cured to the corresponding age were taken out from the constant temperature and humidity curing box, and the flexural strength test was carried out using a flexural and compression integrated testing machine. The flexural test loading speed was 50N / s±5N / s, and the average flexural strength of a group of three prism specimens was taken as the experimental result. When the strength of one of the three prism specimens is outside the range of ±15% of the mean, this data was removed and the mean was recalculated; when the strength of two of the three prism specimens is outside the range of ±15% of the mean, this group of data is invalid, and the specimens of this ratio should be taken again for testing.
[0169] refer to Figure 8, is the 28-day compression ratio of the composite mortar of VAE latex powder and rubber powder at each fiber ratio. It can be found from the figure that after the mixed VAE latex powder and rubber powder are added, the 28-day compression ratio of the engineering geopolymer composite mortar of each fiber ratio decreases to a certain extent. This shows that with the addition of mixed VAE latex powder and rubber powder, the toughness of the engineering geopolymer composite material will be improved. The reasons for this phenomenon may be as follows: First, the VAE latex powder is hydrated in the slurry to form a flexible network structure, which improves the toughness of the composite material and reduces the compression ratio of the composite material; second, the rubber powder forms an elastomer with the hydration product of the geopolymer composite material after hardening, which can absorb and disperse stress, so that the compression ratio of the engineering geopolymer composite material is reduced and the toughness is enhanced; third, both VAE latex powder and rubber powder can improve the bonding interface between the geopolymer slurry and quartz sand, enhance the stress transfer of the composite material under load, and improve the toughness of the composite material and reduce the compression ratio.
[0170] refer to Fig.11 , is the compression-fold ratio of engineering geopolymer composite mortar after 28 days of mixing PVA latex powder and rubber powder. It can be seen from the figure that with the addition of mixed PVA latex powder and rubber powder, the compression-fold ratio of the composite mortar decreases, but the difference in compression-fold ratio when the PVA latex powder is 1% and 2% is not significant. This shows that with the addition of mixed PVA latex powder and rubber powder, the toughness of engineering geopolymer composite mortar has been significantly improved. This may be because the water retention effect of PVA latex powder and the filling effect of rubber powder can optimize the pore structure inside the composite material, enhance the toughness of the composite material, and reduce the compression-fold ratio of the composite material.
[0171] (6) Bending toughness study
[0172] The three-point bending test is used to determine the bending toughness of engineering geopolymer composite materials. The test is carried out on a universal testing machine, and the loading is carried out according to the displacement control method. The loading rate is 0.5mm / min. The corresponding data is collected by computer, and the load-deflection curve is drawn to analyze the bending toughness.
[0173] refer to Fig.12a, is the load-deflection curve of the engineering geopolymer composite mortar sample at 28 days when mixed with 3% VAE latex powder and 3% rubber powder. It can be seen from the figure that the peak load is the largest in the PVA2 group, followed by the PVA1 group and the PP1+1 group, and finally the POM1+1 group. The largest fracture deflection is in the PVA2 group, the smallest is in the PVA1 group, and the PP1+1 group is slightly smaller than the POM1+1 group. It can be seen from the figure that among the four fiber ratios, only the PVA1 group suddenly fails after reaching the peak load, and the other three groups have a relatively obvious strain hardening stage, and have obvious ductility in the strain softening stage after the strain hardening stage, which shows that under this mixed rubber powder ratio, the PVA2 group, the PP1+1 group and the POM1+1 group all have good bending toughness. However, under this mixed rubber powder ratio, the peak load of the PVA2 group is only 3200N, which means that the mechanical strength of the PVA2 group is relatively poor at this time.
[0174] refer to Figure 12b , is the load-deflection curve of engineering geopolymer composite mortar at 28 days when mixed with 5% VAE latex powder and 3% rubber powder. It can be seen from the figure that the peak load and fracture deflection are the largest in the PVA2 group, the peak load and fracture deflection are the smallest in the PVA1 group, and the peak load and fracture deflection of the PP1+1 group are greater than those of the POM1+1 group. Among the four groups of fiber ratios, except for the PVA1 group, the PVA2 group, the PP1+1 group and the POM1+1 group all show good bending toughness.
[0175] contrast Fig.12a and Figure 12b It can be found that when mixed VAE latex powder and rubber powder are added to the engineering geopolymer composite material, the four groups of fiber ratios can obviously show the strain hardening stage, indicating that the bending toughness of the four fiber ratios is good at this time, but the PVA1 group will be quickly destroyed after the peak load, and the ductility is insufficient. The remaining fiber ratios will fluctuate and decrease after the peak load, and the ductility is good.
[0176] refer to Fig.13a , which shows the load-deflection curve of engineering geopolymer composite mortar at 28 days when mixed with 1% PVA latex powder and 3% rubber powder. It can be seen from the figure that the four groups of fibers all have a relatively obvious strain hardening stage, but there is a large difference in the fracture deflection of each group. The fracture deflection of the PVA1 group is the smallest, the fracture deflection of the POM1+1 group is slightly larger than that of the PVA1 group, the fracture deflections of the PVA2 group and the PP1+1 group are much larger than the other two groups, and the fracture deflection of the PVA2 group is the largest.
[0177] refer to Fig.13b, which is the load-deflection curve of mortar samples with different fiber ratios after 28 days of mixing 2% PVA latex powder and 3% rubber powder. It can be seen from the figure that the four fiber ratios all have a relatively obvious strain hardening stage, while the peak load of the PVA2 group is the largest, and the fracture deflection is only greater than that of the POM1+1 group. Overall, the load-deflection curves of the four curves are relatively neat, and the overall difference is not large, which shows that the bending toughness of the PVA2 group has a more obvious decrease compared with other rubber powder dosages, while the PVA1 group, PP1+1 group and POM1+1 group have little change compared with the other groups.
[0178] contrast Fig.13a and Fig.13b It can be found that as the mixed rubber powder increases from 1% PVA latex powder to 2% PVA latex powder, the flexural toughness of each fiber ratio decreases to a certain extent. This may be because the increase in the amount of PVA latex powder leads to an increase in the internal porosity of the mortar samples of each fiber ratio, which in turn causes a certain degree of decrease in the flexural toughness of each ratio.
[0179] (7) Microstructure research
[0180] Small samples of engineering geopolymer specimens of corresponding ages were taken as the samples to be observed, and the samples were sealed and stored in anhydrous ethanol to terminate their hydration. During the test, the samples were first dried in an oven for 24 hours and then sprayed with gold. The microscopic morphology of the samples was observed using the German ZEISS GeminiSEM 300.
[0181] refer to Fig.14a , is the 7-day SEM image of the PVA1 group without glue powder addition. It can be seen that the morphology of the PVA1 group without glue powder addition on the geopolymer matrix is close to that of the neat slurry, that is, there is some gel-like substance and a small amount of pores and cracks. However, it can be seen that the PVA fibers are twisted. This may be because when the specimen is subjected to external load, the fibers absorb energy and break, causing the fiber morphology itself to change.
[0182] refer to Fig.14b , is the 7-day SEM image of the PVA1 group when 3% VAE latex powder was added. After the addition of the latex powder, the PVA fibers are still well combined with the geopolymer matrix, and a large amount of material is attached to the PVA fibers, but tiny pores can be seen on the surface of most of the gel.
[0183] refer to Fig.14c , is the 7-day SEM image of the PVA1 group when 1% PVA latex powder was added. It can be seen from the figure that a large amount of substances are adsorbed on the PVA fibers, and there are a large number of grooves on the surface of the PVA fibers along the fiber axis. This may indicate that the surface of the PVA fibers is damaged during the separation process from the geopolymer matrix.
[0184] contrast Fig.14a -c. After being added, the latex powder dissolves in water to form a coating layer wrapped around the surface of the fiber or geopolymer raw material, which changes the interface characteristics of the fiber and the geopolymer matrix, slows down the occurrence of the geopolymerization reaction, and reduces the mechanical properties of the EGC material. At the same time, it improves the interface bonding between the fiber and the geopolymer matrix, forming a synergistic structure of fiber-latex powder-geopolymer matrix, which increases the fracture energy of the EGC material and improves the bending toughness of the EGC material.
[0185] Example 6
[0186] This embodiment provides a small diameter drainage pipe prepared by using the fiber reinforced geopolymer provided by the present invention.
[0187] The size and mold of the small-diameter drainage pipe are designed and prepared, and the fiber-reinforced geopolymer provided by the present invention is poured into the prefabricated pipe mold, and bubbles are removed. After demoulding and curing for 7 to 28 days, the small-diameter drainage pipe is obtained.
[0188] refer to Figure 15-16 , which are the cross-sectional view and longitudinal cross-sectional view of the pipeline respectively, in which 1 is the FRP socket and 2 is the EGC pipeline; the socket between the pipelines is made of fiber reinforced plastics (FRP) material, which can withstand greater strain than steel sockets, and has viscoelasticity and good elastic-plasticity, and has a closer contact with the pipeline, reducing the possibility of water seepage and leakage at the pipeline connection, avoiding the risk of rust on the steel socket, and increasing the stability and durability of the overall pipeline structure.
[0189] refer to Fig.17 , the small diameter drainage pipe provided in this embodiment is the overall structure of the pipe. The use of EGC material to prepare the drainage pipe can be done without reinforcement or with less reinforcement, which can reduce the construction process and improve the construction efficiency. And due to the use of FRP socket, the overall stability and durability of the pipe are improved, and the structure is more stable.
[0190] In the absence of conflict, the above embodiments and features in the embodiments may be combined with each other.
[0191] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A fiber-reinforced geopolymer, characterized in that: The invention comprises the following components in parts by weight: 250 to 300 parts of mineral powder, 200 to 220 parts of fly ash, 670 to 730 parts of quartz sand, 120 to 150 parts of alkali activator, 7.6 to 24 parts of fiber, 3.5 to 34.9 parts of latex powder and 20.9 to 41.9 parts of rubber powder, and also comprises the following preparation steps: adding mineral powder and fly ash in a cement mortar mixer in sequence, stirring at a low speed, and mixing evenly; slowly adding fiber while stirring and dry mixing for a first preset time, and then adding quartz sand, latex powder and rubber powder, and adding water and stirring evenly, so as to obtain fiber-reinforced geopolymer.
2. The fiber-reinforced geopolymer according to claim 1, characterized in that The fiber is at least one of polyvinyl alcohol fiber, polypropylene fiber and polyoxymethylene fiber.
3. The fiber-reinforced geopolymer according to claim 1, characterized in that The latex powder is PVA latex powder or VAE latex powder.
4. The fiber-reinforced geopolymer according to claim 1, characterized in that The mineral powder is S95 grade ground slag powder with a density of 2.88g / cm 3 , with a specific surface area of 440m 2 / kg.
5. The fiber-reinforced geopolymer according to claim 1, characterized in that The fly ash is selected from Grade II fly ash, with a density of 2.24 g / cm 3 , with a specific surface area of 400m 2 / kg.
6. The fiber-reinforced geopolymer according to claim 2, characterized in that The fiber content is the wet bulk volume content, and the fiber is polyvinyl alcohol fiber.
7. The fiber-reinforced geopolymer according to claim 6, characterized in that The mass concentration ratio of the PVA latex powder and the rubber powder is (1-2):3, wherein the PVA latex powder is added in a proportion calculated based on the total mass of the mineral powder and the fly ash, and the rubber powder is added in a proportion calculated based on the mass of the quartz sand.
8. The fiber-reinforced geopolymer according to claim 1, characterized in that The particle size of the quartz sand is 20 to 40 meshes.
9. Use of the fiber-reinforced geopolymer according to any one of claims 1 to 8 in the preparation of building materials.
10. A drainage pipe, characterized in that: The fiber-reinforced geopolymer according to any one of claims 1 to 8 is poured into a prefabricated pipe mold, bubbles are removed, and the mold is demoulded and cured for 7 to 28 days to obtain the drainage pipe.
Citation Information
Patent Citations
Kaolin-slag base geological polymer compound cementing material with enhanced composite organic macromolecule and preparation method thereof
CN101560068A
Geopolymer / waste rubber powder compound dry powder material and preparation method thereof
CN103693932A
Modified alkali-activated cementing material and preparation method thereof
CN105461265A
Geopolymer-fiber road pavement mending material and preparation method thereof
CN105712669A
Rapid curing geopolymer mortar composition and method for reparing and reinforcing road side ditch, median strip and kerb using the same
KR102160181B1